Composite material, method for producing composite material, and terminal

By forming a silver layer composite coating composed of carbon particles on the blank of the composite material, and using pulse plating technology, the problem of insufficient surface smoothness of the composite material is solved, the wear resistance is improved and the silver layer is prevented from falling off, achieving more Efficient processing stability.

CN119317739APending Publication Date: 2025-01-14DOWA METALTECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380043970.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-04
Filing Date
2023-10-02
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The surface smoothness of the composite coating of existing composite materials is insufficient, which may cause the silver layer to fall off during bending processing, causing pollution problems.

Method used

By forming a silver layer composite coating composed of carbon particles on the blank, the silver crystal crystallographic size is controlled to be more than 40nm and less than 70nm, the surface Vickers hardness exceeds 90, and the precipitation and dissolution process are alternately carried out during the electroplating process. , forming a smooth composite coating.

Benefits of technology

It significantly improves the wear resistance of the composite material, and effectively suppresses the fall of the silver layer during bending processing, avoiding contamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317739A_ABST
    Figure CN119317739A_ABST
Patent Text Reader

Abstract

A composite material in which a composite film comprising a silver layer containing carbon particles is formed on a blank, the crystallite size of silver in the composite film being more than 40 nm and 70 nm or less, and the arithmetic average roughness Ra ([mu] m) of the composite film being 2.0 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite material formed by forming a predetermined composite film on a blank, a method for producing the same, and more particularly to a composite material used as a material for sliding electrical contact parts such as switches and connectors, and a method for producing the same. Background Art

[0002] Conventionally, as materials for sliding electrical contact parts such as switches and connectors, silver (Ag)-plated materials, in which conductor materials such as copper (Cu) and copper alloys are plated with silver, are used to prevent oxidation of the conductor materials due to heat during sliding.

[0003] However, silver plating is soft and easily wears, and generally has a high friction coefficient, so there is a problem that it is easy to peel off due to sliding. In order to solve this problem, a method has been proposed in which a composite film is formed on a conductor blank by electroplating, in which graphite particles among carbon particles such as graphite and carbon black having excellent wear resistance and lubricity are dispersed in a silver base to improve wear resistance (for example, refer to Patent Documents 1 and 2).

[0004] In addition, the applicant conducted research with the purpose of providing a composite material with excellent wear resistance, and conceived of a composite material having a composite coating (AgC layer) with small silver crystallite size, high hardness and excellent wear resistance by electroplating using a silver plating solution containing specific components, and disclosed it as Patent Document 3.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 9-7445

[0008] Patent Document 2: Japanese Patent Application Publication No. 2007-16250

[0009] Patent document 3: WO2021 / 261066 pamphlet Summary of the invention

[0010] Problem that the invention aims to solve

[0011] As described above, the composite material (composite coating) disclosed in Patent Document 3 is excellent in wear resistance.

[0012] However, according to further research by the inventors, it is known that in the technology disclosed in Patent Document 3, the surface smoothness of the composite coating is insufficient. For example, when the composite material is bent into the shape of a terminal using a mold, the convex portion of the surface of the composite coating strongly contacts the mold, and stress is concentrated on the portion, which may fall off. If this happens, when the user uses the composite material (during bending, etc.), the detached silver may also become a pollutant (pollution source) and contaminate the equipment.

[0013] The present invention is completed under the above-mentioned conditions, and the problem to be solved is to provide a composite material having a composite coating containing carbon particles in a silver layer formed on a blank, the composite material having excellent wear resistance and inhibiting the silver from falling off from the composite coating (AgC layer) during bending.

[0014] Solutions for solving problems

[0015] The present inventors have conducted in-depth research to achieve the above-mentioned problem. As a result, they found that by using the same specific plating solution as Patent Document 3 and forming a composite coating by pulse electroplating, a composite material having excellent wear resistance and inhibiting the shedding of silver from the composite coating during bending can be obtained, thereby completing the present invention.

[0016] That is, the present invention is as follows.

[0017] [1] A composite material, comprising a composite coating composed of a silver layer containing carbon particles formed on a blank, wherein the silver crystallite size of the composite coating is greater than 40 nm and less than 70 nm, and the arithmetic mean roughness Ra (μm) of the composite coating is less than 2.0 μm.

[0018] [2] The composite material according to [1], wherein the blank is made of Cu or a Cu alloy.

[0019] [3] The composite material according to [1] or [2], wherein the Vickers hardness of the surface of the composite film is 90 or higher.

[0020] [4] The composite material according to any one of [1] to [3], wherein the silver crystallite size of the composite coating is 50 to 66 nm.

[0021] [5] The composite material according to any one of [1] to [4], wherein a base layer composed of at least one selected from the group consisting of Cu, Ni, Sn, and Ag is formed between the raw material and the composite film.

[0022] [6] A method for producing a composite material, wherein a composite coating composed of a silver layer containing carbon particles is formed on a blank by electroplating in a silver plating solution containing carbon particles, wherein the silver plating solution contains a compound A represented by the following general formula (I), and pulse electroplating is performed as the electroplating:

[0023]

[0024] (In the general formula (I), m is an integer from 1 to 5, Ra is a carboxyl group, Rb is an aldehyde group, a carboxyl group, an amino group, a hydroxyl group or a sulfonic acid group, Rc is hydrogen or any substituent, when m is 2 or more, multiple Rb's present may be the same or different from each other, when m is 3 or less, multiple Rc's present may be the same or different from each other, and Ra and Rb are each independently bonded to the benzene ring via a divalent group consisting of at least one selected from the group consisting of -O- and -CH2-.).

[0025] [7] The method for producing a composite material according to [6], wherein in the pulse electroplating, a composite coating precipitation step of depositing silver on the blank to form a silver-based composite coating containing carbon particles and a composite coating dissolution step of dissolving a portion of the silver-based composite coating are alternately repeated, and the pulse electroplating is carried out under the following conditions:

[0026] The composite film deposition process is carried out at a current density of 1.5 to 5.0 A / dm 2 Apply current.

[0027] The composite coating dissolution process: the current density is -12 to -2.5A / dm 2 Apply current.

[0028] The composite film precipitation step and the composite film dissolution step are alternately repeated 300 to 10,000 times.

[0029] The ratio (Tp / Td) of the time Tp for applying the current in the composite film deposition step to the time Td for applying the current in the composite film dissolution step is set to 2-8.

[0030] [8] The method for producing a composite material according to [6] or [7], wherein the concentration of the carbon particles in the silver plating solution is 10 g / L or more and 150 g / L or less.

[0031] [9] A terminal for an electric contact, using the composite material according to any one of [1] to [5] as its constituent material.

[0032] Effects of the Invention

[0033] According to the present invention, there is provided a composite material having a composite coating including a silver layer and carbon particles formed on a blank, the composite material having excellent wear resistance and preventing silver from falling off from the composite coating during bending. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is a schematic cross-sectional view explaining the silver shedding evaluation test during bending in the example. DETAILED DESCRIPTION

[0035] Hereinafter, embodiments of the present invention will be described.

[0036] [1. Method for producing composite material]

[0037] In the method for producing a composite material of the present invention, pulse plating is performed as electroplating in a silver plating solution containing carbon particles and a specific compound, thereby forming a composite coating containing carbon particles in a silver layer on a blank. The following describes each structure of the method for producing a composite material.

[0038] <<1-1. Billet>>

[0039] As the constituent material of the blank on which the composite coating is formed, it is preferred that the material can be silver-plated and has the conductivity required by the material of the sliding contact parts such as switches and connectors, and further from the viewpoint of cost, as the constituent material, Cu (copper) and Cu alloys are preferred. As the above-mentioned Cu alloy, from the viewpoints of conductivity, strength, etc., it is preferred that the alloy is composed of Cu and at least one selected from the group consisting of Si (silicon), Fe (iron), Mg (magnesium), P (phosphorus), Ni (nickel), Sn (tin), Co (cobalt), Zn (zinc), Be (beryllium), Pb (lead), Te (tellurium), Ag (silver), Zr (zirconium), Cr (chromium), Al (aluminum) and Ti (titanium), and inevitable impurities. The amount of Cu in the Cu alloy is preferably 85% by mass or more, more preferably 92% by mass or more (the amount of Cu is preferably 99.95% by mass or less).

[0040] As described later, the blank is preferably used for the purpose of the terminal (as a composite material formed with a composite coating), but sometimes the blank itself is directly the shape of the purpose, and sometimes the blank is a flat shape (flat plate shape, etc.), which is formed into the shape of the purpose after becoming a composite material. From the viewpoint of exerting the effect of the present invention, the blank is preferably in a flat shape. In this case, the longer flat plate-shaped blanks can be concentrated (continuously) for electroplating, so the productivity of the composite material is excellent. In addition, if the arithmetic mean roughness Ra (μm) of the blank is large, the arithmetic mean roughness Ra (μm) of the composite coating formed thereon may also become large, so it is preferred that the Ra of the blank is small, specifically 0.5μm or less. The Ra of the blank is preferably 0.05 to 0.2μm.

[0041] <<1-2. Formation of base layer>>

[0042] In the manufacturing method of the composite material of the present invention, a base layer can be formed on the blank, and the base layer is subjected to the electroplating described later. The base layer is formed for the purpose of preventing the copper of the blank from diffusing to the surface of the coating and oxidizing, deteriorating the conductivity of the composite material, and improving the adhesion of the composite film. As the constituent metal of the base layer, at least one metal or alloy selected from the group consisting of Cu, Ni, Sn and Ag can be listed. It should be noted that the base layer can be a single layer composed of Cu, Ni, Sn, Ag or their alloys alone or a layer (laminated structure) composed of them, and the formation of the base layer can be the entire surface layer of the blank or a part thereof according to the purpose of the composite material manufactured.

[0043] The method for forming the base layer is not particularly limited, and the base layer can be formed by electroplating using a plating solution containing ions of the above-mentioned metal constituents by a known method, or by sequentially stacking layers of metals constituting the target alloy layer and then performing reflow soldering (heat treatment). It should be noted that, from the perspective of wastewater treatment costs, the above-mentioned plating solution is preferably substantially free of cyanide.

[0044] <<1-3. Ag strike plating>>

[0045] Preferably, before forming the composite coating on the blank, a very thin intermediate layer is formed by Ag strike plating to improve the adhesion between the blank and the composite coating. It should be noted that when forming a base layer on the blank, it is preferred to perform Ag strike plating on the base layer to improve the adhesion between the base layer and the composite coating. As a method for implementing the Ag strike plating, any conventionally known method can be adopted without particular limitation as long as the effect of the present invention is not impaired. From the viewpoint of wastewater treatment cost, the plating solution used for the Ag strike plating is preferably substantially free of cyanide.

[0046] <<1-4. Electroplating (Pulse Plating)>>

[0047] In the manufacturing method of the composite material of the present invention, in a specific silver plating solution, for the blank described above, after the formation of a base layer and / or the formation of an intermediate layer based on Ag strike plating as needed, pulse electroplating is carried out as electroplating, thereby forming a composite coating containing carbon particles in the silver layer on the blank.

[0048] <1-4-1. Silver plating solution>

[0049] The silver plating solution contains silver ions, a specific compound A and carbon particles.

[0050] (1-4-1-1. Silver ions)

[0051] The silver plating solution contains silver ions. From the viewpoint of the formation speed of the composite film and the viewpoint of suppressing uneven appearance of the composite film, the concentration of silver in the silver plating solution is preferably 5 to 150 g / L, more preferably 10 to 120 g / L, and most preferably 20 to 100 g / L.

[0052] (1-4-1-2. Compound A)

[0053] Next, compound A is represented by the following general formula (I).

[0054]

[0055] In the general formula (I), m is an integer of 1 to 5, Ra is a carboxyl group, Rb is an aldehyde group, a carboxyl group, an amino group, a hydroxyl group or a sulfonic acid group, and Rc is hydrogen or an arbitrary substituent. Ra and Rb can each independently be bonded to the benzene ring via a divalent group consisting of at least one selected from the group consisting of -O- and -CH2-. Examples of the above divalent groups include -CH2-CH2-O-, -CH2-CH2-CH2-O-, (-CH2-CH2-O-) n (n is an integer greater than or equal to 2).

[0056] It is believed that compound A is adsorbed on the surface of the precipitated silver to inhibit the crystal growth of silver, thereby reducing the crystallite size of silver in the composite film formed by electroplating. Thus, a composite material having excellent hardness and thus excellent wear resistance is obtained.

[0057] In the above general formula (I), when m is 2 or more, multiple Rb groups may be the same or different from each other, and when m is 3 or less, multiple Rc groups may be the same or different from each other. As for Rc, the above-mentioned "optional substituent" includes an alkyl group having 1 to 10 carbon atoms, an alkylaryl group, an acetyl group, a nitro group, a halogen group, and an alkoxy group having 1 to 10 carbon atoms.

[0058] From the viewpoint of suppressing uneven appearance of the composite coating and appropriately controlling the size of silver crystallites in the formed composite coating, the concentration of compound A in the silver plating solution is preferably 2 to 250 g / L, more preferably 3 to 200 g / L.

[0059] (1-4-1-3. Carbon particles)

[0060] The silver plating solution contains carbon particles. If the silver plating solution contains carbon particles, the carbon particles are rolled into the silver substrate when a composite coating (silver plating) is formed on the blank by electroplating. If the composite coating contains carbon particles, the wear resistance of the composite material is improved. From the viewpoint of exerting such a function, the carbon particles are preferably graphite particles. The cumulative 50% particle size (D50) of the carbon particles measured by a laser diffraction / scattering particle size distribution measuring device on a volume basis is preferably 0.5 to 15 μm, and more preferably 1 to 10 μm, from the viewpoint of being easily rolled into the silver plating. Furthermore, the shape of the carbon particles is generally spherical, scaly, amorphous, etc., and is not particularly limited. From the perspective of improving the wear resistance of the composite material by smoothing the surface of the composite coating, it is preferably a scaly shape. It should be noted that the carbon particles being rolled into the silver substrate means that, in addition to the situation where the carbon particles are completely buried in the silver substrate, it also includes the situation where only a portion of the carbon particles is contained in the silver substrate and a portion of the carbon particles are exposed outside the silver substrate.

[0061] In addition, from the viewpoint of the wear resistance of the composite material obtained by forming a composite coating on the blank using a silver plating solution and the viewpoint that there is a limit to the amount of carbon particles that can be introduced into the composite coating, the amount of carbon particles in the silver plating solution is preferably 10 to 150 g / L, more preferably 15 to 120 g / L, and most preferably 30 to 100 g / L.

[0062] In addition, it is preferred to perform an oxidation treatment before the carbon particles are put into the plating solution, thereby removing the lipophilic organic matter adsorbed on the surface of the carbon particles. Such lipophilic organic matter includes aliphatic hydrocarbons such as alkanes and olefins, and aromatic hydrocarbons such as alkylbenzenes. As an oxidation treatment of carbon particles, in addition to wet oxidation treatment, dry oxidation treatment using O2 gas or the like can also be used, but from the perspective of mass production, wet oxidation treatment is preferably used, and carbon particles with a large surface area can be uniformly treated by wet oxidation treatment. As a method of wet oxidation treatment, a method of adding an appropriate amount of oxidant after suspending the carbon particles in water can be used. As an oxidant, nitric acid, hydrogen peroxide, potassium permanganate, potassium persulfate, sodium perchlorate and other oxidants can be used. It is believed that the lipophilic organic matter attached to the carbon particles is oxidized by the added oxidant to become a form that is easily soluble in water and is appropriately removed from the surface of the carbon particles. In addition, after the wet oxidation treatment, filtration is performed, and then the carbon particles are washed with water, thereby further improving the effect of removing lipophilic organic matter from the surface of the carbon particles. By oxidizing the carbon particles, lipophilic organic substances such as aliphatic hydrocarbons and aromatic hydrocarbons can be removed from the surface of the carbon particles. According to the analysis of the gas heated at 300° C., the gas generated by heating the carbon particles after the oxidation treatment at 300° C. contains almost no lipophilic aliphatic hydrocarbons such as alkanes and olefins, and lipophilic aromatic hydrocarbons such as alkylbenzenes. Even if some aliphatic hydrocarbons and aromatic hydrocarbons are contained in the carbon particles after the oxidation treatment, the carbon particles can be uniformly dispersed in the silver plating solution used in the present invention. However, it is preferred that the carbon particles do not contain hydrocarbons with a molecular weight of 160 or more, and the gas intensity (purge and trap gas chromatography mass spectrometry analysis intensity) generated by heating at 300° C. for hydrocarbons with a molecular weight of less than 160 in the carbon particles is 5,000,000 or less.

[0063] (1-4-1-4. Complexing agent)

[0064] The silver plating solution used in the present invention preferably contains a complexing agent. The complexing agent complexes the silver ions in the silver plating solution to improve the stability of the ions. Through this action, the solubility of silver in the solvent constituting the plating solution is improved.

[0065] A wide range of complexing agents having the above functions can be used as complexing agents. From the viewpoint of the stability of the complex formed, compounds having a sulfonic acid group are preferred. As compounds having a sulfonic acid group, alkylsulfonic acids having 1 to 12 carbon atoms, alkanolsulfonic acids having 1 to 12 carbon atoms, and hydroxyarylsulfonic acids can be cited. Specific examples of these compounds include methanesulfonic acid, 2-propanesulfonic acid, and phenolsulfonic acid.

[0066] From the viewpoint of stabilization of silver ions, the amount of the complexing agent in the silver plating solution is preferably 30 to 200 g / L, more preferably 50 to 120 g / L.

[0067] (1-4-1-5. Other additives)

[0068] As other additives, for example, the silver plating solution used in the present invention may contain a brightener, a curing agent, and a conductive salt. Examples of the curing agent include carbon sulfide compounds (e.g., carbon disulfide), inorganic sulfur compounds (e.g., sodium thiosulfate), organic compounds (sulfonates), selenium compounds, tellurium compounds, and metals of Group 4B or 5B of the periodic table. Examples of the conductive salt include potassium hydroxide and the like.

[0069] (1-4-1-6.Solvent)

[0070] The solvent constituting the silver plating solution is mainly water. Water is preferred because of its excellent solubility of (complexed) silver ions and other components contained in the plating solution and its low environmental load. In addition, a mixed solvent of water and alcohol can also be used as a solvent.

[0071] <1-4-2. Pulse plating conditions>

[0072] In the present invention, pulse plating is performed as electroplating using the silver plating solution described above. The pulse plating performed in the present invention is to perform electroplating by changing the sign of the current applied periodically (alternatingly). By such pulse plating, the formation of the plated film (precipitation of metallic silver while entraining carbon particles) and dissolution are repeated alternately to form a smooth composite coating with few bumps. In addition, by the function of compound A, the crystallite size of silver in the composite coating is suppressed to be smaller.

[0073] In the technology disclosed in Patent Document 3, the inventor has studied the reasons why the smoothness of the surface of the composite coating is insufficient, and the results are considered to be as follows. If the silver plating solution contains a prescribed additive (benzoic acid compound) as in Patent Document 3, it is considered that the plating is performed in a state where the additive is adsorbed on carbon particles. It is believed that there are carbon particles that are involved in the silver substrate but partially exposed on the surface of the composite coating being formed, but the above-mentioned additive is adsorbed on the carbon particles, and Ag is precipitated and grows on the exposed and adsorbed portion of the carbon particles. It is generally believed that Ag is precipitated on Ag as the silver substrate being formed, but the above-mentioned additive adsorbed on the above-mentioned carbon particles becomes the starting point for Ag precipitation.

[0074] It is believed that if the precipitation of Ag is carried out in this way, the part from which the Ag precipitated on the carbon particles grows becomes a convex part, i.e., a non-smooth composite coating with many concave-convex surfaces is formed. In the pulse plating of the present invention, during the formation of the silver substrate comprising carbon particles (referred to as the composite coating precipitation process), the silver plating solution also contains a prescribed benzoic acid compound as in patent document 3, so it is believed that the same situation as above will occur. However, by utilizing the process of dissolving a part of the silver substrate with the negative current of pulse plating (referred to as the composite coating dissolving process), the silver substrate formed by the precipitation and growth of Ag on the blank, which is the starting point of the formation of the above-mentioned convex part, is dissolved. In addition, it is believed that in the growth of the Ag precipitated on the carbon particles and the growth of the silver substrate, the latter is faster. It is believed that by alternately and repeatedly carrying out such a composite coating dissolving process and the composite coating precipitation process, a composite coating with a smooth surface is formed in the present invention. Below, the embodiment of the pulse plating in the present invention is described in detail.

[0075] (1-4-2-1. Cathode and anode)

[0076] The raw material to be plated is the cathode, and the silver electrode plate, for example, which dissolves and provides silver ions, is the anode.

[0077] (1-4-2-2. Current density)

[0078] The cathode and the anode are immersed in a silver plating solution (plating bath), and current is applied to perform silver plating. The plating current here is positive in the composite film deposition step and negative in the composite film dissolution step.

[0079] In the composite film deposition step, the current density is preferably 1.5 to 5.0 A / dm from the viewpoint of the composite film formation speed and the viewpoint of suppressing the uneven appearance of the composite film. 2 , more preferably 2.0 to 4.0 A / dm 2 In the composite film dissolution step, the current density is preferably -12 to -2.5 A / dm from the viewpoint of the productivity of the composite film of the entire pulse plating and the smoothness of the formed composite film. 2 , more preferably -11 to -6 A / dm 2 .

[0080] From the viewpoint of forming a smooth composite film and the viewpoint of the productivity of the composite film, the absolute value of the ratio of the current density Ed in the composite film dissolution step to the current density Ef in the composite film formation step (Ed / Ef) is preferably 1 to 10, more preferably 1.5 to 7, and particularly preferably 2 to 5. The above ratio (Ed / Ef) may be varied within the above range in each step of the alternating repetition of the two steps in pulse plating.

[0081] (1-4-2-3. Pulse waveform, number of repetitions of the alternation between the precipitation step and the dissolution step, and time allocation of the two steps)

[0082] The waveform during pulse plating is not particularly limited, for example, a sine wave or a rectangular wave can be used. The number of repetitions of the alternately performed composite coating precipitation step and the composite coating dissolution step can be appropriately adjusted according to the thickness of the composite coating to be formed, the ratio of the average time of each of the two steps, etc., for example, it can be set to 300 to 10,000 times (meaning that when the alternate repetition of the composite coating precipitation step and the dissolution step is set to once, it is repeated 300 to 10,000 times). The number of repetitions is preferably 800 to 6000 times.

[0083] In addition, from the viewpoint of both the productivity of the composite film and the smoothness of the composite film, the ratio of the time Tp for applying the current in each composite film precipitation step to the time Td for applying the current in each composite film dissolution step (Tp / Td) is preferably 2 to 8, and more preferably 3 to 6. It should be noted that the above two steps are alternately repeated to form the composite film, but the above ratio (Tp / Td) can also be changed within the above range in each repeated step (the composite film precipitation step and the composite film dissolution step are each one step).

[0084] Furthermore, the time Tp is preferably 0.2 to 2 seconds, more preferably 0.4 to 1.2 seconds. The time Td is preferably 0.05 to 1 second, more preferably 0.1 to 0.4 seconds. With regard to the time Tp and the time Td, each step of the alternating repetition of the composite coating precipitation step and the dissolution step may be varied within the above range.

[0085] (1-4-2-4. Temperature, stirring, and area to be plated)

[0086] From the viewpoint of production efficiency of plating and preventing excessive evaporation of liquid, the temperature (plating temperature) of the plating bath (silver plating solution) during pulse plating is preferably 15°C to 50°C, more preferably 20°C to 45°C. From the viewpoint of implementing uniform plating, the stirring speed of the plating bath at this time is preferably 200rpm to 550rpm, more preferably 350rpm to 500rpm. In addition, the object of plating can be the entire surface layer of the blank or a part of the surface layer of the blank according to the purpose of the composite material manufactured.

[0087] <<1-5. Treatment for partial removal of carbon particles from the composite coating surface>>

[0088] A composite coating is formed on the blank by the electroplating (pulse plating) described above. On the surface of the composite coating, there are carbon particles that are entangled (buried) in the silver substrate and difficult to fall off, and carbon particles that are attached to the surface and are easier to fall off than being entangled. The latter may contaminate the equipment during the bending process of the composite material. Therefore, it is preferred to clean and remove such carbon particles. One of the cleaning methods is to perform ultrasonic cleaning on the surface of the composite coating. Ultrasonic cleaning is preferably performed at 20 to 100 kHz for 1 to 300 seconds. In addition, as another cleaning method, electrolytic cleaning can be cited. At this time, electrolytic cleaning is preferably performed at 1 to 30 A / dm 2 Perform for 10 to 300 seconds.

[0089] [2. Composite materials]

[0090] The following is an explanation of an embodiment of the composite material of the present invention. The composite material is a composite material formed by forming a composite coating composed of a silver layer containing carbon particles on a blank, the crystallite size of the silver of the composite coating is greater than 40nm and less than 70nm, and the arithmetic mean roughness Ra (μm) of the composite coating is 2.0μm. The composite material can be manufactured, for example, by the manufacturing method of the composite material of the present invention. The following is an explanation of each composition of the composite material.

[0091] <<2-1. Billet>>

[0092] The blank is the same as the blank described above for the method for producing the composite material of the present invention. That is, as the constituent material of the blank, Cu (copper) and Cu alloys are preferred, and as the Cu alloy, from the viewpoints of conductivity and strength, it is preferred that the alloy is composed of Cu and at least one selected from the group consisting of Si (silicon), Fe (iron), Mg (magnesium), P (phosphorus), Ni (nickel), Sn (tin), Co (cobalt), Zn (zinc), Be (beryllium), Pb (lead), Te (tellurium), Ag (silver), Zr (zirconium), Cr (chromium), Al (aluminum) and Ti (titanium), and inevitable impurities.

[0093] <<2-2. Basal layer>>

[0094] A base layer can be formed between the blank and the composite coating for various purposes. As the constituent metal of the base layer, at least one metal or alloy selected from the group consisting of Cu, Ni, Sn and Ag can be listed. For example, for the purpose of preventing the copper in the blank from diffusing to the surface of the composite coating and deteriorating the conductivity, it is preferred to form a base layer composed of Ni. For the purpose of preventing the zinc in the blank from diffusing to the surface of the composite coating when the blank is a copper alloy containing zinc such as brass, it is preferred to form a base layer composed of Cu. For the purpose of improving the adhesion of the composite coating to the blank, it is preferred to form a base layer composed of Ag. The thickness of the base layer is not particularly limited, and from the perspective of its function and cost, it is preferably 0.1 to 2 μm, and more preferably 0.2 to 1.5 μm. In addition, the terminals of electrical / electronic components mostly use materials that have been plated with Sn or reflow-plated Sn containing a Cu substrate or a Ni substrate (a stacked structure of a Cu substrate, a Ni substrate, and a Sn substrate from the blank side), and such a stacked structure base layer can also be formed in the present invention. Therefore, in the present invention, the base of the composite coating may have a single layer composed of Cu, Ni, Sn, Ag or their alloys alone or a layer (laminated structure) of a combination of these. In addition, for example, the composite coating specified in the present invention may be formed on the electrical contact portion of the blank (either a base layer or not), and a reflow-plated Sn base layer may be formed on the wire fastening portion (without forming a composite coating), etc., and different layers may be formed depending on the location.

[0095] <<2-3. Composite coating>>

[0096] The composite coating formed on the blank is composed of a silver layer containing carbon particles. In the silver layer, the carbon particles are (preferably roughly evenly) dispersed in a base composed of silver. It should be noted that when Ag strike plating is performed before forming the composite coating, there is an intermediate layer formed by the strike plating between the blank (or the base layer described later) and the composite coating, but in most cases it is very thin and cannot be distinguished from the composite coating. In addition, the composite coating can be formed on the entire surface layer of the blank, or on a part of the surface layer.

[0097] <2-3-1. Crystallite size and Vickers hardness>

[0098] The crystallite size of silver in the composite film in the embodiment of the composite material of the present invention is relatively small, exceeding 40nm and being less than 70nm. In this way, due to the small crystallite size, the hardness of the composite film is high due to the Hall-Petch relationship (generally, the smaller the grains of the metal material, the greater the strength). Due to the high hardness, the composite film is difficult to be ground, and the wear resistance of the composite material becomes higher. It should be noted that, compared with the composite film of the composite material disclosed in Patent Document 3, the hardness is sometimes slightly lower, but the composite film of the composite material of the present invention also has wear resistance that is not a problem in practical use. When the crystallite size is too small, although the hardness of the composite film is high and the wear resistance is excellent, due to the large number of grain boundaries, it is easy to cause the diffusion of the constituent metals such as Cu from the base material into the interior of the composite film when heated, and the conductivity is reduced (poor reliability). For this reason, in the composite material of the present invention, the crystallite size of silver in the composite film is set to a size exceeding 40nm. From the viewpoint of taking into account both wear resistance and the aforementioned reliability, the crystallite size is preferably 45 to 68nm, and more preferably 50 to 66nm.

[0099] It should be noted that in the present invention, in order to reduce the deviation caused by the crystal plane, the crystallite size of silver (111) plane and (222) plane is averaged (added and divided by 2) to obtain the value obtained. A more detailed method for measuring the crystallite size is described in the examples.

[0100] As described above, the composite coating has a small crystallite size and therefore has high hardness, and specifically, its Vickers hardness Hv is preferably 90 or more, and more preferably 100 to 180. Details of the method for measuring the Vickers hardness Hv will be described in the Examples.

[0101] <2-3-2. Arithmetic mean roughness Ra>

[0102] The composite coating of the composite material of the present invention has an arithmetic mean roughness Ra (μm) of 2.0 μm or less. In the composite material of the present invention having such a composite coating with a smooth surface, the shedding of silver from the composite coating during bending is effectively suppressed. A composite material having such a composite coating with a smooth surface, a small silver crystallite size, and excellent wear resistance can be manufactured, for example, by the manufacturing method of the composite material of the present invention.

[0103] From the viewpoint of suppressing the loss of silver from the composite coating during bending, the composite coating preferably has an arithmetic mean roughness Ra of 1.5 μm or less. It is difficult to produce a composite coating having a very small arithmetic mean roughness Ra in practice, but the above Ra is more preferably 0.2 to 1.2 μm.

[0104] It is known that the thicker the composite film of a composite material, the larger its arithmetic mean roughness Ra. The present inventors conducted a study and found that the arithmetic mean roughness Ra (μm) divided by the 0.5 power of the thickness of the composite film (μm) is 0.5 ) can well correct the increase in the arithmetic mean roughness Ra caused by the thickness of the composite film (it can be easily used as an adjustment index that eliminates the influence of the thickness of the composite film on Ra). From the viewpoint of suppressing the shedding of silver from the composite film during bending and the viewpoint that it is difficult to manufacture a composite film with a very small arithmetic mean roughness Ra, the arithmetic mean roughness Ra (μm) of the composite material of the present invention is divided by the 0.5 power of the thickness of the composite film (μm 0.5 ) is preferably 0.05 to 0.5 (μm 0.5 ), more preferably 0.1 to 0.3 (μm 0.5 ).

[0105] <2-3-3. Carbon particles>

[0106] The carbon particles are the same as the carbon particles described above in the method for producing the composite material of the present invention. That is, the carbon particles are preferably graphite particles, and their shapes are generally spherical, scaly, amorphous, etc., without particular limitation, and are preferably scaly in shape from the perspective of improving the wear resistance of the composite material by making the surface of the composite coating smooth.

[0107] In addition, from the viewpoint of wear resistance of the composite material, the average primary particle size of the carbon particles is preferably 0.2 to 15 μm, and more preferably 0.4 to 10 μm. It should be noted that the average primary particle size refers to the average value of the major diameter of the particles, and the major diameter refers to the length of the longest line segment that can be drawn from the particle (between two points on the outer circumference of the particle) in the image (plane) obtained by observing the carbon particles in the composite film of the composite material at an appropriate observation magnification. In addition, the major diameter is obtained for more than 50 particles.

[0108] <2-3-4. Composition of composite film and area ratio of carbon particles>

[0109] The composite film in the embodiment of the composite material of the present invention contains carbon particles as described above. From the viewpoint of wear resistance and conductivity of the composite material, the carbon content in the composite film is preferably 1 to 50% by mass, more preferably 1.5 to 40% by mass, and further preferably 2 to 35% by mass. In addition, the elemental composition of the composite film in the embodiment of the composite material of the present invention is typically substantially composed of silver and carbon.

[0110] In addition, the proportion (area ratio) of carbon particles in the surface of the composite coating containing carbon particles becomes an index of wear resistance. From the viewpoint of wear resistance, a certain ratio is required. On the other hand, when the ratio is too high, there are problems in terms of conductivity. From the viewpoint of the balance between these wear resistance and conductivity, the above-mentioned area ratio is 5 area % or more and 80 area % or less, preferably 8 area % or more and 60 area % or less, more preferably 10 area % or more and 50 area % or less, and further preferably 22 area % or more and 40 area % or less. As described in the description of the method for manufacturing the composite material of the present invention, sometimes there are carbon particles on the surface of the composite coating that are only attached and easily fall off. In this case, after implementing the same ultrasonic cleaning treatment as described in <<1-5. Partial removal of carbon particles on the surface of the composite coating>>, the area ratio of the carbon particles on the surface of the composite coating is obtained. The details of the method for determining the above-mentioned area ratio are described in the examples.

[0111] <2-3-5. Thickness of composite coating>

[0112] The thickness of the composite coating is not particularly limited, but from the viewpoint of wear resistance and conductivity, the minimum thickness is preferably used. In addition, even if the thickness is too large, the effect of the composite coating is saturated, and the cost of raw materials increases. From the above viewpoints, the thickness of the composite coating is preferably 0.5 μm or more and 45 μm or less, more preferably 1 μm or more and 35 μm or less, and further preferably 2 μm or more and 25 μm or less. The details of the method for measuring the thickness of the composite coating are described in the examples.

[0113] <<2-4. Delamination of silver from the composite coating during bending>>

[0114] As described above, in the embodiment of the composite material of the present invention, the arithmetic mean roughness Ra of the composite coating surface is as small as 2.0 μm or less, which inhibits the silver from falling off from the composite coating during bending. Specifically, in the evaluation test of silver falling off during bending in the embodiments described later, when the peeled carbon tape is subjected to EDS analysis using an energy dispersive X-ray analyzer, when the total of the detected elements is set to 100% by mass, the proportion of Ag is preferably 15% by mass or less, more preferably 10% by mass or less, further preferably 7% by mass or less, and particularly preferably 4% by mass or less. In addition, it is difficult to make the above-mentioned Ag proportion 0, and it is usually 0.2% or more by mass.

[0115] [3.Terminal]

[0116] The wear resistance of the composite material according to the embodiment of the present invention is excellent, and the silver peeling from the composite coating film during bending is less. Therefore, it is suitable as a constituent material for terminals for electrical contacts, especially terminals (manufactured by bending) in electrical contact components such as switches and connectors that slide during their use.

[0117] Examples

[0118] Hereinafter, examples of the composite material of the present invention and its manufacturing method will be described in detail.

[0119] [Example 1] <Preparation and oxidation treatment of carbon particles>

[0120] 80 g of flaky graphite particles (PAG-3000 manufactured by Nippon Graphite Industry Co., Ltd.) with an average particle diameter of 4.8 μm as carbon particles were added to 1.4 L of pure water, and the mixture was heated to 50 °C while stirring. It should be noted that the average particle diameter is the particle diameter at which the cumulative value based on volume measured using a laser diffraction scattering type particle size distribution measuring device (MT3300 (LOW-WET MT3000 II Mode) manufactured by Microtrac BEL Co., Ltd.) is 50%. Then, 0.6 L of an aqueous solution of 0.1 mol / L potassium persulfate (270 g / mol) as an oxidant was slowly added dropwise to the mixture, and the mixture was stirred for 2 hours to perform the oxidation treatment. Then, filtration separation was performed using filter paper, and the obtained solid matter was washed with water. The washing with water was repeated until the conductivity of the filtrate after washing reached 10 μS / cm or less.

[0121] For the carbon particles before and after the oxidation treatment, a purge-trap-gas chromatography mass spectrometry analysis device (a device combined with JHS-100 manufactured by Nippon Analytical Industry Co., Ltd. as a thermal desorption device and GCMS QP-5050A manufactured by Shimadzu Corporation as a gas chromatography mass spectrometer) was used to analyze the gas generated by heating at 300 °C. As a result, it was found that by the above oxidation treatment, lipophilic aliphatic hydrocarbons (such as nonane, decane, 3-methyl-2-heptene, etc.) and lipophilic aromatic hydrocarbons (such as xylene, etc.) attached to the carbon particles were removed.

[0122] <Ag strike plating>

[0123] A plate made of a Cu-Ni-Sn-P alloy with a length of 5.0 cm, a width of 5.0 cm, and a thickness of 0.2 mm was prepared. This plate is NB-109EH manufactured by Dowa Metaltech Co., Ltd., and is a copper alloy plate containing 1.0 mass% of Ni, 0.9 mass% of Sn, and 0.05 mass% of P, with the balance being Cu and inevitable impurities. In addition, the arithmetic mean roughness Ra of the surface of this plate measured by the method described later is 0.1 μm.

[0124] Using this sheet material as a blank, using this blank as a cathode, and using an iridium oxide mesh electrode plate (wherein the titanium mesh blank has been coated with iridium oxide) as an anode, in a sulfonic acid-based silver strike plating solution containing methanesulfonic acid as a complexing agent (DAIN SILVER GPE-ST manufactured by Daiwa Kasei Co., Ltd., substantially free of cyanide, silver concentration 3 g / L, methanesulfonic acid concentration 42 g / L), at a liquid temperature of 25°C and a current density of 5 A / dm 2 Perform electroplating (silver strike plating) for 120 seconds. It should be noted that silver strike plating is performed on the entire surface layer of the blank.

[0125] <AgC coating>

[0126] Add the carbon particles (graphite particles) that have undergone the above oxidation treatment to a sulfonic acid-based silver plating solution containing 30 g / L of silver and 60 g / L of methanesulfonic acid with methanesulfonic acid as a complexing agent (DAIN SILVER GPE-HB manufactured by Daiwa Kasei Co., Ltd. (containing compound A corresponding to the general formula (I) at a concentration of 4.2 g / L, and the solvent is mainly water)) to prepare a sulfonic acid-based silver plating solution containing 50 g / L of carbon particles, 30 g / L of silver, and 60 g / L of methanesulfonic acid. This silver plating solution is substantially free of Sb and cyanide.

[0127] Next, use the blank that has undergone the above Ag strike plating as a cathode and a silver electrode plate as an anode. In the above sulfonic acid-based silver plating solution containing carbon particles, while stirring at 400 rpm using a stirrer, perform pulse reverse plating at a temperature of 25°C (using a current density of 3.0 A / dm 2 ·a composite film deposition process of 0.8 seconds and a composite film dissolution process of current density -9.0 A / dm 2 ·0.2 seconds as one step, and repeat 4000 steps) to obtain a composite material in which a composite film (AgC electroplating film) containing carbon particles is formed on the blank. It should be noted that in the implementation of the above pulse reverse plating, a bipolar power supply device BP4610 manufactured by Noise Research Institute Co., Ltd. is used, and the pulse waveform is rectangular (the rise and fall times of the waveform are approximately 4 μs).

[0128] <Ultrasonic cleaning treatment>

[0129] For the surface of the composite film of the obtained composite material, use an ultrasonic cleaner (VS-100III manufactured by AS ONE, output power 100 W, tank size: 140 mm in length × 240 mm in width × 100 mm in depth), set the liquid medium as water, and perform ultrasonic cleaning treatment at 28 kHz for 4 minutes to obtain the composite material of Example 1.

[0130] The production conditions and the like of the above composite materials are summarized in Table 1 below together with the production conditions and the like of Example 2, Example 3, and Comparative Examples 1 to 3 described later.

[0131] [Table 1]

[0132]

[0133] The composite material of Example 1 obtained was evaluated as follows.

[0134] <Thickness of composite film>

[0135] The thickness of the composite film (the range of a circle with a diameter of 0.2 mm in the center of a surface with a length of 5.0 cm and a width of 5.0 cm) was measured with a fluorescent X-ray film thickness meter (FT9450 manufactured by Hitachi High-Technologies Corporation) and the result was 21.2 μm. It should be noted that it is difficult to detect C atoms (of carbon particles) using a fluorescent X-ray film thickness meter, and the thickness is determined by detecting Ag atoms, but the thickness thus determined is regarded as the thickness of the composite film in the present invention.

[0136] <Vickers hardness Hv of composite coating surface>

[0137] The Vickers hardness Hv of the composite coating surface was measured using a microhardness tester (HM221 manufactured by Mitutoyo Corporation) by applying a load of 0.01 N to the flat portion of the composite material for 15 seconds in accordance with JIS Z2244, and the average value of three measurements was used.

[0138] Regarding the later-described embodiments 2, 3 and comparative example 3, the thickness of the composite coating is thin, and the hardness cannot be measured by the above method, so the Vickers hardness is not measured. Regarding the later-described comparative examples 1 and 2, the thickness of these composite coatings is also thin, but for the purpose of Vickers hardness measurement, the composite material is prepared by changing only the plating time from comparative examples 1 and 2 (the plating time is set to 1200 seconds in both comparative examples 1 and 2). For the composite material having a thickness of about 20 μm of the obtained composite coating, the Vickers hardness is measured by the above method.

[0139] <Area Ratio of Carbon Particles on Composite Film Surface>

[0140] Using a table microscope (TM4000 Plus manufactured by Hitachi High-Technologies Co., Ltd.), the image (1 field of view) of the reflected electron composition (COMPO) of the surface of the composite coating was binarized at an acceleration voltage of 5 kV, and the area ratio of carbon on the surface of the composite coating was calculated using GIMP 2.10.10 (image analysis software). Specifically, when the highest brightness of all pixels is set to 255 and the lowest brightness is set to 0, the grayscale is binarized in such a way that pixels with a brightness of less than 127 are black and pixels with a brightness of more than 127 are white, and the grayscale is separated into the silver part (white part) and the carbon particle part (black part), and the ratio Y / X of the number of pixels Y of the carbon particle part to the number of pixels X of the entire image is calculated as the area ratio (%) of the carbon particles on the surface. The area ratio of carbon particles is 33%.

[0141] <Silver crystallite size of composite coating>

[0142] The surface of the composite coating was subjected to X-ray diffraction measurement in accordance with JIS H7805: 2005 using an X-ray diffractometer (RINT-2000 manufactured by Rigaku Corporation) (Cu Kα-ray tube, tube voltage: 30 kV, tube current: 10 mA, step length: 0.01°, scanning range: 2θ=0°~155°, scanning speed: 5° / min, measurement time: about 31 minutes, peak of (111) plane: 2θ=38.5~39.3°, peak of (222) plane: 2θ=81.9~82.8°). The full width at half maximum (FWHM: Full Width at Half Maximum) was calculated using X-ray analysis software (PDXL manufactured by Rigaku Corporation) based on the detected peaks of the (111) plane and (222) plane of silver, and the crystallite size in each crystal plane of silver was calculated using the Scherrer formula. In order to reduce the deviation caused by the crystal plane, the average value of the crystallite size of the silver (111) plane and the silver (222) plane was taken as the crystallite size of silver. The crystallite size was 63.3 nm.

[0143] In addition, the Scherrer formula is as follows.

[0144] D=K·λ / (β·cosθ)

[0145] D: Crystallite size

[0146] K: Scherrer constant, set to 0.9

[0147] λ: wavelength of X-rays, CuKα rays, so 1.54 angstroms

[0148] β: Full width at half maximum (FWHM) (rad)

[0149] θ: Measurement angle (deg)

[0150] <Arithmetic mean roughness Ra of composite coating>

[0151] The image of the surface of the composite film was taken at a magnification of 1000 times using a laser microscope (VKX-110 manufactured by KEYENCE Co., Ltd.), and the arithmetic mean roughness Ra, a parameter representing the surface roughness (of the entire observed surface of the composite film) was calculated based on JIS B0601 (2001) using an analytical program (VK-HIXA version 3.8.0.0 manufactured by KEYENCE Co., Ltd.). The result was 1.00 μm. In addition, the arithmetic mean roughness Ra (μm) was calculated by dividing the thickness of the composite film to the power of 0.5 (μm). 0.5 ) and the result is 0.22(μm 0.5 ).

[0152] <Composition of composite film>

[0153] The composite film was observed using a tabletop microscope (TM4000 Plus manufactured by Hitachi High-Technologies Corporation) as an electron microscope at an acceleration voltage of 15 kV and magnified to 1000 times. In the observation area (one field of view), EDX analysis was performed using an energy dispersive X-ray analyzer (AztecOne manufactured by Oxford Instruments Corporation) attached to the tabletop microscope, and the detected elements were used as the composition of the composite film. As a result, it was found that no elements other than Ag and C were detected, and the composite film was substantially formed of Ag and C.

[0154] <Evaluation of Wear Resistance>

[0155] From the composite material obtained in Example 1, a flat test piece of 2.0 cm in width x 3.0 cm in length was cut out.

[0156] On the other hand, as a convex-shaped indenter that slides relative to the flat test piece (plate), the following indenter was prepared.

[0157] The copper alloy plate material used as the blank in Example 1 was subjected to a stamping process (so-called embossing process) with an inner diameter of 1.0 mm. The processed product was used as a blank and subjected to the same silver strike plating as in Example 1. The silver strike plating was applied to the entire surface layer of the blank.

[0158] Next, the Ag strike-plated blank was used as a cathode and the silver electrode plate was used as an anode. In an Ag-Sb alloy plating solution (cyanide bath) containing 10 mass % of sodium silver cyanide, 30 mass % of sodium cyanide and 50 mL / L of Nissinbright N (brightener, containing 6 mass % of antimony trioxide) (manufactured by Nikkei Corporation), electroplating was performed at a temperature of 15° C. (current density 1.2 A / dm 2 · 37.5 minutes). As a result, a test piece with an indentation on which an AgSb plating layer containing 2 mass % of Sb, having a Vickers hardness (Hv) of 180 and a thickness of 20 μm was formed was obtained.

[0159] The test piece with the indentation was used as a convex indenter in the following sliding wear test.

[0160] The convex part of the test piece with the indentation was brought into contact with the flat test piece by a sliding wear tester (CRS-G2050-DWA manufactured by Yamazaki Seiki Laboratories, Ltd.), and the test piece with the indentation was pressed against the flat test piece with a certain load (5N) while continuing the reciprocating sliding motion (sliding distance 10mm (i.e., 1 reciprocating motion is 20mm), sliding speed 10mm / s), and a wear test was performed to confirm the wear state of the test piece with the indentation and the flat test piece, thereby evaluating the wear resistance. As a result, after 20,000 reciprocating sliding motions, the center of the sliding marks of the test piece with the indentation (indenter) and the flat test piece (plate) were observed at a magnification of 200 times using a microscope (VHX-1000 manufactured by KEYENCE Co., Ltd.), and it was confirmed that the (brown) blank (copper alloy plate) was not exposed, and it was known that the composite material of Example 1 had excellent wear resistance.

[0161] <Silver shedding evaluation test during bending>

[0162] A bending test piece with a width of 10 mm was cut from the obtained composite material with the length direction being TD (direction perpendicular to the rolling direction) and the width direction being LD (rolling direction). For the bending test piece, a 90° W bending test according to JIS H3130 was carried out with LD as the bending axis (Bad Way bending (BW bending)) and a bending radius R = 0.2 mm.

[0163] Reference Figure 1 The 90° W-bending test will be described. Figure 1 It means the upper die fixture J UP And lower die fixture J DOWN A schematic cross-sectional view of a test piece T clamped to produce a peak M and a valley V. UPAnd lower die fixture J DOWN When the test piece T was bent by clamping it, the load applied to the upper and lower clamps was monitored so that the upper and lower clamps would not further apply load to the bent test piece T.

[0164] After the test, the test piece T and the upper mold fixture J UP Contact surface F UP , carbon tape C (carbon double-sided tape 7322 for SEM manufactured by Nissin EM Co., Ltd.: width 12 mm) was used to paste the tape, and then peeled off by manually pulling it in the vertical upward direction. It should be noted that the carbon tape C was pasted in a manner that protruded 1 mm on both sides of the width direction of the test piece T.

[0165] In the carbon tape C after peeling, the test piece T and the upper mold fixture J UP Contact surface F UP In the experiment, observation was performed using a desktop microscope (TM4000 Plus manufactured by Hitachi High-Technologies Corporation) as an electron microscope at an acceleration voltage of 15 kV and magnified to 100 times, starting from the central position in the width direction corresponding to the bent portion becoming the valley V of the test piece T and proceeding 2 mm in the length direction toward the central position in the width direction corresponding to the bent portion becoming the peak M.

[0166] Then, EDS analysis was performed using an energy dispersive X-ray analyzer (AztecOne manufactured by Oxford Instruments Co., Ltd.) attached to the above-mentioned tabletop microscope in the observed area (one field of view) of the carbon tape C. As a result, Ag and C were detected, and the amount of Ag was 3.80 mass %.

[0167] The evaluation results of the above composite materials are summarized in Table 2 below together with the evaluation results of Examples 2 and 3 and Comparative Examples 1 to 3 described later.

[0168] [Table 2]

[0169]

[0170] [Example 2]

[0171] A composite material of Example 2 was prepared in the same manner as in Example 1 except that the composite film deposition step and the composite film dissolution step of pulse reverse plating were repeated 2000 times.

[0172] [Example 3]

[0173] A composite material of Example 3 was prepared in the same manner as in Example 1 except that the composite film deposition step and the composite film dissolution step of pulse reverse plating were repeated 1000 times.

[0174] [Comparative Example 1]

[0175] A composite material of Comparative Example 1 was prepared in the same manner as in Example 1 except that the following normal electroplating was performed instead of pulse reverse plating, and various evaluations were performed on the composite material in the same manner as in Example 1.

[0176] The blank was subjected to Ag strike plating in the same manner as in Example 1. The blank subjected to Ag strike plating was used as a cathode and a silver electrode plate was used as an anode. In the same sulfonic acid silver plating solution containing carbon particles as in Example 1, the silver plating solution was stirred at 400 rpm by a stirrer at a temperature of 25°C and a current density of 3 A / dm 2 Electroplating was performed for 600 seconds to obtain the composite material of Comparative Example 1.

[0177] The composite material of Comparative Example 1 had a small silver crystallite size in the composite film, high Vickers hardness, and excellent wear resistance, but had a large arithmetic mean roughness Ra on the composite film surface, and much silver fell off during bending.

[0178] [Comparative Example 2]

[0179] The time for applying current was set to 300 seconds, and as the silver plating solution, a sulfonic acid-based silver plating solution containing carbon particles obtained by adding carbon particles (graphite particles) subjected to the same oxidation treatment as in Example 1 to a sulfonic acid-based silver plating solution containing methanesulfonic acid at a concentration of 100 g / L and a silver concentration of 30 g / L (DAIN SILVER GPE-PL manufactured by Yamato Chemical Industry Co., Ltd. (does not contain the compound A corresponding to the general formula (1) and the solvent is water)) was used. In addition, the composite material was prepared in the same manner as in Comparative Example 1 except that the plating time was set to 300 seconds.

[0180] The composite material of Comparative Example 2 was evaluated in the same manner as in Example 1. The results showed that the silver crystallite size of the composite film of the composite material was large, the Vickers hardness was low, and the wear resistance was poor. On the other hand, the silver fell off less during bending.

[0181] [Comparative Example 3]

[0182] As the silver plating solution, the same sulfonic acid silver plating solution containing carbon particles as used in Comparative Example 2 was used, and the number of repetitions of the composite coating precipitation process and the composite coating dissolution process of pulse reverse plating was set to 2000 times. Otherwise, the composite material of Comparative Example 3 was prepared in the same manner as in Example 1.

[0183] The composite material was evaluated in the same manner as in Example 1. As a result, the composite material had a large silver crystallite size and poor wear resistance, while silver shedding during bending was small.

[0184] Description of Reference Numerals

[0185] T test piece

[0186] C Carbon tape

[0187] M Peak

[0188] V Tanibe

[0189] F UP Surface in contact with the upper die fixture

[0190] J UP Upper die fixture

[0191] J DOWN Lower die fixture

Claims

1. A composite material, comprising a composite coating formed on a blank and comprising a silver layer containing carbon particles, The silver crystallite size of the composite coating is greater than 40 nm and less than 70 nm, The composite film has an arithmetic mean roughness Ra (μm) of 2.0 μm or less.

2. The composite material according to claim 1, wherein The blank is made of Cu or a Cu alloy.

3. The composite material according to claim 1 or 2, wherein: The Vickers hardness of the surface of the composite film is 90 or higher.

4. The composite material according to claim 1 or 2, wherein: The silver crystallite size of the composite coating is 50-66 nm.

5. The composite material according to claim 1 or 2, wherein: An underlayer composed of at least one selected from the group consisting of Cu, Ni, Sn, and Ag is formed between the ingot and the composite film.

6. A method for producing a composite material, comprising forming a composite coating composed of a silver layer containing carbon particles on a blank by electroplating in a silver plating solution containing carbon particles, The silver plating solution contains a compound A represented by the following general formula (I): Pulse plating is performed as the electroplating, In the general formula (I), m is an integer of 1 to 5, Ra is a carboxyl group, Rb is an aldehyde group, a carboxyl group, an amino group, a hydroxyl group or a sulfonic acid group, Rc is hydrogen or any substituent, When m is 2 or more, the multiple Rb may be the same or different from each other. When m is 3 or less, a plurality of Rc's may be the same or different from each other. Ra and Rb each independently may be bonded to the benzene ring via a divalent group consisting of at least one selected from the group consisting of -O- and -CH2-.

7. The method for producing a composite material according to claim 6, wherein: In the pulse plating, a composite coating deposition step of depositing silver on the blank to form a silver base containing carbon particles and a composite coating dissolution step of dissolving a portion of the silver base of the composite coating are alternately repeated, and the following conditions are used in the pulse plating: The composite film deposition process is carried out at a current density of 1.5 to 5.0 A / dm 2 applying an electric current; The composite coating dissolution process: the current density is -12 to -2.5A / dm 2 applying an electric current; The composite film precipitation step and the composite film dissolution step are alternately repeated 300 to 10,000 times; The ratio (Tp / Td) of the time Tp for applying the current in the composite film deposition step to the time Td for applying the current in the composite film dissolution step is set to 2-8.

8. The method for producing a composite material according to claim 6 or 7, wherein: The concentration of the carbon particles in the silver plating solution is 10 g / L or more and 150 g / L or less.

9. A terminal for an electric contact, using the composite material according to claim 1 or 2 as its constituent material.

Citation Information

Patent Citations

  • Sliding contact of electric equipment

    JP1997007445A

  • Composite plated material and method for producing the same

    JP2007016250A

  • Composite material, composite material manufacturing method, and terminal

    WO2021261066A1